2013
DOI: 10.1371/journal.pone.0076538
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Ameliorates Liver Fibrosis via Mediating Nitric Oxide Synthase in Rats with Non-Alcoholic Steatohepatitis-Related Liver Fibrosis

Abstract: BackgroundSimvastatin exerts pleiotropic effects on cardiovascular system. However, its effect on non-alcoholic fatty liver disease, especially the liver fibrosis, remains obscure. We aimed to clarify the relationship between simvastatin and liver fibrosis both in vivo and in vitro.MethodsA High-fat diet was given to establish rat models with non-alcoholic steatohepatitis (NASH)-related liver fibrosis and simvastatin (4mg·kg-1·d-1) was administrated intragastrically until hepatic histological findings confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 36 publications
6
100
0
2
Order By: Relevance
“…These findings are in accordance with previous researches. 6,7 The results of the present study also showed significant increase in serum levels of blood lipids, TNF-α, IL-1β, IL-6, leptin and visfatin with increased insulin resistance index (HOMA-IR) and decreased adiponectin level in NASH rats, thus confirming the role of the above factors on the pathogenesis of NASH.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in accordance with previous researches. 6,7 The results of the present study also showed significant increase in serum levels of blood lipids, TNF-α, IL-1β, IL-6, leptin and visfatin with increased insulin resistance index (HOMA-IR) and decreased adiponectin level in NASH rats, thus confirming the role of the above factors on the pathogenesis of NASH.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies found that high-fat and high-cholesterol diet induce liver steatosis, steatohepatitis, fibrosis, necrosis and cause excess oxidative stress in the liver. 6,7 Besides, dyslipidaemia, insulin resistance, obesity and elevated serum aminotransferases accompany these liver changes.…”
Section: Introductionmentioning
confidence: 99%
“…Macrovesicular steatosis are more abundant than the microvesicular as was observed above. The findings is in consonant with that of human and animal forms of non-alcoholic fatty liver disease NAFLD which is characterized by a mixed macro and microvesicular type of hepatic steatosis [22][23][24][25][26][27][28] .The histology of the liver tissue of rats fed with high fat diet exhibited significant alteration in the architecture of the liver tissue. The alteration include micro and macro vascular steatosis, increased fatty infiltration, inflammation , sinusoidal dilation, degeneration of veins and vacuolization as compared to normal liver histology in figure A,C.…”
Section: Resultssupporting
confidence: 77%
“…1,2 Fibrosis associated with NASH has been suggested to be the physiological consequence of chronic hepatic injury, necrosis, and inflammation as well as unbalanced intrahepatic lipid metabolism (steatosis), insulin resistance, oxidative stress, and lipid peroxidation. [3][4][5] Different lipid molecules may mediate the pathogenesis and the progression of NASH. To date, the identity of a dominant lipid molecule/s, which causes liver lipotoxicity, is still unknown.…”
mentioning
confidence: 99%